2013
DOI: 10.1002/jcp.24314
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone abrogates TLR4 activation in prostate smooth muscle cells contributing to the preservation of a differentiated phenotype

Abstract: Prostate smooth muscle cells (pSMCs) are capable of responding to inflammatory stimuli by secreting proinflammatory products, which causes pSMCs to undergo dedifferentiation. Although it has been proposed that androgens decrease proinflammatory molecules in many cells and under various conditions, the role of testosterone in the prostate inflammatory microenvironment is still unclear. Therefore, our aim was to evaluate if testosterone was able to modulate the pSMCs response to bacterial LPS by stimulating prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
(46 reference statements)
1
17
0
Order By: Relevance
“…TLR4 is also actively involved in bacterial invasion, and TLR4/cAMP-mediated immune function can expel UPEC from infected uroepithelial cells [35]. Leimgruber et al showed that the presence of testosterone could downregulate TLR4 activation and prevent the dedifferentiated (myofibroblast-like) phenotype of prostate smooth muscle cells stimulated by bacterial LPS [36, 37]. They also demonstrated that testosterone reduces cytokine secretion after LPS challenge, which is consistent with our results with UPEC-infected testosterone-treated cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR4 is also actively involved in bacterial invasion, and TLR4/cAMP-mediated immune function can expel UPEC from infected uroepithelial cells [35]. Leimgruber et al showed that the presence of testosterone could downregulate TLR4 activation and prevent the dedifferentiated (myofibroblast-like) phenotype of prostate smooth muscle cells stimulated by bacterial LPS [36, 37]. They also demonstrated that testosterone reduces cytokine secretion after LPS challenge, which is consistent with our results with UPEC-infected testosterone-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone may reduce IL-6 and TNF-α production after LPS challenge by preventing Iκβ-alpha degradation and NF-κβ nuclear translocation [36]. Although the anti-inflammatory effects of testosterone in variety of tissues with microbial infection are well known, the mechanism of androgen action on prostate inflammatory response to bacterial LPS was not very clear.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies have found that not only the epithelial but also stromal cells of the prostate express TLR4 both in vivo (Quintar et al, ; Gatti et al, ) and in vitro (Leimgruber et al, , ). Additional works have documented that all TLRs are expressed in prostatic stromal cells (Penna et al, ).…”
Section: Host Defense Molecules In the Prostate Glandmentioning
confidence: 82%
“…It has been reported that the stromal compartment critically influences the initiation and/or maintenance of proliferative pathologies in the prostate gland (Tuxhorn et al, ; Antonioli et al, ; Penna et al, ). Indeed, we described a rapid stromal response to bacterial infection, characterized mainly by hypertrophy and the acquisition of a secretory phenotype in smooth muscle cells (Quintar et al, ) which was then reproduced in vitro (Leimgruber et al, , , ). Related to this, much evidence suggests that smooth muscle cells are metabolically dynamic cells with the potential to express and secrete numerous highly active signaling proteins (Singer et al, ).…”
Section: Prostatic Inflammation and Its Impact On Prostatic Tissuesmentioning
confidence: 99%
“…They also extended the observations to determine the effects of castration, and showed that RELA (therein referred to as NFkB/p65), in combination with CD14 and MyD88, coordinates the adaptation of epithelial and smooth-muscle cells to androgen deprivation, including the ability to produce surfactant protein D (SP-D) [48], [49].…”
Section: Discussionmentioning
confidence: 93%